Exploring juventology: unlocking the secrets of youthspan and longevity programs - Brandhorst, Sebastian; Longo, Valter D. (Frontiers in Aging, 2024)
In recent decades, the study of biological aging has evolved from simplistic theories like the free radical theory to more complex and nuanced perspectives. In particular, the identification of evolutionary conserved genes and signaling pathways that can modulate both lifespan but also healthspan has resulted in the expanding understanding of the link between nutrients, signal transduction proteins, and aging along with substantial support for the existence of multiple “longevity programs,” which are activated based on the availability of nutrients. Periodic fasting and other dietary restrictions can promote entry into a longevity program characterized by cellular protection and optimized function, and the activation of regenerative processes that lead to rejuvenation. This review discusses the idea of juventology, a novel field proposing the existence of longevity programs that can maintain organisms in a highly functional state for extended periods of time. Drawing upon research on Saccharomyces cerevisiae and other model organisms, the review explores the distinctiveness of juventology from traditional aging-centered views. The focus on the "age of youth" challenges conventional thinking and opens new avenues for understanding and extending the period of peak functionality in organisms. Thus, a “juventology”‐based strategy can complement the traditional gerontology approach by focusing not on aging but on the longevity program affecting the life history period in which mortality is very low and organisms remain youthful, healthy, and fully functional.